Rhizomatic Learning Paths of Education Researchers: Assemblages and Becomings - Kairiené, Aida; Mažeikienė, Natalija; Rupšienė, Liudmila (Journal of Education Culture and Society, 2026)
Aim. The aim of the research – to highlight the assemblages and becomings in rhizomatic learning of research methodologies among education researchers, identifying rhizomatic learning paths.Methods. Thinking with theory approach. This research is based on Gilles Deleuze and Félix Guattari’s (2004) poststructuralist philosophy and assemblage theory, as well as Alecia Y. Jackson and Lisa A. Mazzei’s (2023) thinking with theory approach. Cartography. The learning trajectories of education researchers have been depicted in rhizomatic maps based on Deleuze and Guattari’s (2004) rhizome principles: connectivity and heterogeneity, multiplicity and rupture, and cartography. Rhizoanalysis. Rooted in Deleuze and Guattari’s (2004) concepts and the principles of the rhizome, rhizoanalysis (Masny, 2015) was applied to analyse rhizomatic paths of education researchers.Results. The most common assemblages are art-exploration assemblages, more-than-human assemblages, and work-related practice assemblages. The less common assemblages are material-led assemblages and affective (body and emotions) assemblages. During their learning journey, researchers create various becomings, such as becoming-explorer, becoming-artist, or becoming-expert of research methods. The rhizomatic maps disclosed that education researchers develop their learning through Deleuze and Guattari’s (2004) rhizome principles.Conclusions. The findings of this study show that education researchers should strengthen their learning of research methodologies by engaging in more material-led practice, establishing and working in research laboratories, conducting innovative research, and creating new methods themselves.